A comparative study of information processing time in chronic alcoholic and non-alcoholic men - Kaur, Vishavdeep; Walia, Lily; Grewal, Simran; Nagpal, Sangeeta (International Journal of Research in Medical Sciences, 2016)
Background: An impairment in information processing time in chronic alcoholics compared to non-alcoholic men. Information processing time was assessed by using reaction time as a tool. Reaction time involves the central processing to a sensory input and output as execution of movement which may be a success or failure. Methods: Chronic alcoholics were diagnosed on the basis of AUDIT, extensive history and complete examination. Reaction time a tool for assessing information processing time was measured using digital display response time apparatus with a visual stimulus. Results: Visual reaction time for all three colours was increased in chronic alcoholics compared to the non-alcoholic men. Conclusions: This study concludes that with chronic consumption of alcohol there is slow processing of information as well as decrease in efficiency of sensorimotor functioning which is shown by an increased reaction time for visual stimuli.